Serological diagnosis of diarrhoea caused by some representatives of the genera Vibrio and Aeromonas - Khaitovich, A B; Gal'tseva, G V (Journal of hygiene, epidemiology, microbiology, and immunology, 1983)
Various serological methods were used to study 630 blood sera of patients with diarrhoea on whom microorganisms of the genera Vibrio (vibrios of non-01 group, phosphorescent, parahaemolytic and alginolytic vibrios) and Aeromonas were isolated, and also of patients with unconfirmed bacteriological diagnosis, carriers and healthy persons. It has been established that specific antibodies are isolated in 30-50% of cases, most frequently in the agglutination reaction, in PHAR with flagellar erythrocyte diagnostic agent, in the reaction of vibriocidal antibodies using the Takachi apparatus. Serological diagnosis is a subsidiary method promoting the performance of clinico-epidemiological analysis of diseases with diarrhoea.
Keywords: Aeromonas; protilátky bakteriální; hemaglutinační testy; Vibrio Infections; Diarrhea; Hemagglutination Tests; lidé; Antibodies, Bacterial; Vibrio; průjem; Bacterial Infections; aglutinační testy; bakteriální infekce; Agglutination Tests; infekce bakteriemi rodu Vibrio; Humans